Determinants of Marketed Surplus of Milk: A Micro Level Study in Khasi Hills Region of Meghalaya - Das, Mridupaban; Singh, Ram; Feroze, S M; Singh, S Basanta (Indian Journal of Extension Education, 2020)
The dairy sector has been playing a pivotal role in India's socio-economic development by providing employment and income-generating opportunities in the rural areas. At the micro level, it provides livelihood to millions of households. Animal husbandry has a multi-dimensional role in improving the socio-economic condition of the agrarian community. In North eastern states, the development of the livestock sector is very slow, which reflects the less production and consumption of milk. The study investigates the production, consumption, disposal, and factors determining the marketed surplus of milk in the state of Meghalaya. There lie opportunities for value addition and formation of a dairy cooperative or a farmer's producer organization (FPO) for the development of the dairy sector in the state of Meghalaya.